Liquid crystals for IR: Part I – synthesis and properties of perfluoroalkyl or perfluoroalkoxy terminated oligophenyls. Issue 14 (7th December 2020) - Harmata, Piotr; Herman, Jakub; Kula, Przemysław
ABSTRACT: Several homologous series of laterally halogenated and perfluoroalkyl or perfluoroalkoxy terminated oligophenyl derivatives, where the length of the core varies from two to four benzene rings, have been synthesised and mesomorphic properties, phase transition temperatures and enthalpies were determined. The influence of the length of the core, type and position of substituents in the molecular core has been analysed and compared with similarly substituted analogues with conventional chain systems. The lack of aliphatic protons in molecular structure generates unique infrared properties of presented materials and their mixtures. Graphical abstract: uf0001